Longitudinal patterns and predictors of response to standard-of-care therapy in lupus nephritis: data from the Accelerating Medicines Partnership Lupus Network - Peter M. Izmirly; Mimi Y. Kim; Philip M. Carlucci; Katherine Preisinger; Brooke Z. Cohen; Kristina Deonaraine; Devyn Zaminski; Maria Dall’Era; Kenneth Kalunian; Andrea Fava; H. Michael Belmont; Ming Wu; et al. (Arthritis Research & Therapy, 2024)
Abstract Background Leveraging the Accelerating Medicines Partnership (AMP) Lupus Nephritis (LN) dataset, we evaluated longitudinal patterns, rates, and predictors of response to standard-of-care therapy in patients with lupus nephritis. Methods Patients from US academic medical centers with class III, IV, and/or V LN and a baseline urine protein/creatinine (UPCR) ratio ≥ 1.0 (n = 180) were eligible for this analysis. Complete response (CR) required the following: (1) UPCR < 0.5; (2) normal serum creatinine (≤ 1.3 mg/dL) or, if abnormal, ≤ 125% of baseline; and (3) prednisone ≤ 10 mg/day. Partial response (PR) required the following: (1) > 50% reduction in UPCR; (2) normal serum creatinine or, if abnormal, ≤ 125% of baseline; and (3) prednisone dose ≤ 15 mg/day. Results Response rates to the standard of care at week 52 were CR = 22.2%; PR = 21.7%; non-responder (NR) = 41.7%, and not determined (ND) = 14.4%. Only 8/180 (4.4%) patients had a week 12 CR sustained through week 52. Eighteen (10%) patients attained a week 12 PR or CR and sustained their responses through week 52 and 47 (26.1%) patients achieved sustained PR or CR at weeks 26 and 52. Week 52 CR or PR attainment was associated with baseline UPCR > 3 (ORadj = 3.71 [95%CI = 1.34–10.24]; p = 0.012), > 25% decrease in UPCR from baseline to week 12 (ORadj = 2.61 [95%CI = 1.07–6.41]; p = 0.036), lower chronicity index (ORadj = 1.33 per unit decrease [95%CI = 1.10–1.62]; p = 0.003), and positive anti-dsDNA antibody (ORadj = 2.61 [95%CI = 0.93–7.33]; p = 0.069). Conclusions CR and PR rates at week 52 were consistent with the standard-of-care response rates observed in prospective registrational LN trials. Low sustained response rates underscore the need for more efficacious therapies and highlight how critically important it is to understand the molecular pathways associated with response and non-response.